Limitation of the activated partial thromboplastin time as a monitoring method of the direct thrombin inhibitor argatroban. (25th August 2015) - Guy, S.; Kitchen, S.; Maclean, R.; Van Veen, J. J.
Summary: Background: Argatroban is licensed for patients with heparin‐induced thrombocytopenia and monitoring is conventionally by activated partial thromboplastin time (APTT) ratio with a target of 1.5–3.0 and not exceeding 100 s. The APTT may be influenced by coagulopathies, lupus anticoagulant and raised FVIII levels. Variable but not clinically significant sensitivity of APTT reagents to argatroban has been highlighted in other studies. Methods: Residual plasma of 15 patients ( n = 124 samples) was tested on Sysmex ™ CS series using the Hemoclot ® thrombin inhibitor assay (HTI) and APTT ratio (Actin FS and SynthASil). A subgroup from four patients ( n = 31) were tested on ACL TOP ™ to compare the different platforms with the HTI. Spiked normal pooled plasma was tested with Actin FS, Actin FSL, SynthASil and APTT‐SP on their respective platforms (CS5100 ™ and ACL TOP ™ ) to assess reagent sensitivity. Results: Mean concentration of argatroban by HTI assay for patient plasma was 0.47 μ g/mL; the mean APTT ratio using Actin FS was 1.89 and for SynthASil 1.56. There was a poor correlation between APTT and the HTI. In the spiked normal pooled plasma, Actin FS gave a significantly higher APTT ratio than the other three reagents for the various argatroban concentrations. Conclusions: Hemoclot ® thrombin inhibitor assay should be considered in patients on argatroban, particularly if there is concern the APTT may not be reflective of the degree of anticoagulation with argatroban due to other factors including coagulopathies in critically ill patients, the presence of a lupus anticoagulant or very high FVIII levels.